IMPLEMENTASI PENGAWASAN BAPENDA KABUPATEN KAMPAR TERHADAP PEMUNGUTAN PAJAK REKLAME BERDASARKAN PERATURAN DAERAH KABUPATEN KAMPAR NOMOR 14 TAHUN 2011 TENTANG PAJAK REKLAME DI KAMBUPATEN KAMPAR - Yulanda, Resti; Sutrisno, Hafiz; Saputra, Rian Prayudi (Pahlawan Tuanku Tambusai University, 2023)
Advertising tax has great potential with optimal supervision so that there is a lot of misuse of tax collection. There are many illegal objects that do not have permits, one of which is cell phone advertisements on Jalan Sisingamangaraja and several other roads. In controlling activities, there are advertisement users who do not pay taxes. There are two problem formulations, the first is how Bapenda supervises the collection of advertisement tax based on the Kampar Regency Regional Regulation Number 14 of 2011, secondly, what are the obstacles faced by Bapenda in supervising the collection of advertisement tax based on the Kampar Regency Regional Regulation. The research method is (Observation) which takes samples from one population, using questionnaires, interviews as data collection tools, while its nature is analytical descriptive. From the results of the discussion, it was concluded that advertising tax collection had not gone well because many taxpayers had not been registered and several obstacle factors meant that the implementation of collection had not run optimally. Barriers to billboard tax collection are lack of outreach to taxpayers, lack of human resources or the number of members carrying out the collection, and databases. To overcome the obstacles, Bapenda should increase tax collection so that there are no errors in the field with those on computers, Bapenda should increase socialization of the importance of paying taxes, Bapenda should increase the number of tax collection members, Bapenda should recruit experts in the field of informatics to increase the standardization Keyword : Collection, Advertisement Tax, Kampar Regency Bapenda